Using CORPORA in the Language Learning Classroom: Corpus Linguistics for Teachers - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Reviewed by Nur Yigitoglu Department of Applied Linguistics and ESL Georgia State University, USA   The interest in using corpora and corpus-based materials in language teaching and research continues to grow. Over the past few years, research by second language teaching specialists has emphasized the importance of using corpora and corpus-based materials in the second language learning classroom. This is true not only for research articles (Conrad 1999, Cortes 2007), but also for academic conferences such as those organized by the American Association of Corpus Linguistics (AACL). In Using CORPORA in the Language Learning Classroom: Corpus Linguistics for Teachers, Bennett aims to make the ideas of corpus linguistics accessible to second language teachers, graduate students specializing in applied linguistics, and teacher-trainers working with language instructors. The volume is divided into three main parts and eight chapters, and also includes two appendices and a conceptual index.